Effects of Cement Dust on Electrolytes and Osmolality in Serum and Urine of Kufa Cement Factory workers (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cement industry is considered one of the serious pollutants in the environment inducing different kinds ofhealth problems among workers. However, there have been few studies examining the adverse effects ofcement dust on the levels of electrolytes and osmolality among workers. In the current study, we investigatedthe potential impacts of the cement dust on the levels of electrolytes and osmolality in both serum and urineamong workers of Kufa Cement Factory. The workers were grouped into three groups according to theirdepartments. The workers, who were aged between 38-48 years, were grouped into oven workers (N=20),mills workers (N=16) and control workers (N=22). While workers who were aged between 49-59 years,were also grouped into oven workers (N=14), mills workers (N=13) and control workers (N=9). Serumand urine samples were collected from all studied subjects. Regardless of age groups, the results showedthat the levels of serum sodium and potassium were significantly increased among workers at the oven andmills departments compared to the control. While the levels of blood serum calcium and osmolality weresignificantly reduced among workers at the oven and mills departments compared to control group. In theurine samples, the levels of sodium were significantly higher among oven workers compared to the findingsin both mills and control. While the levels of calcium and osmolality were significantly higher in both ovenand mills workers compared to the control.